Laserstrahlsintern von Metallpulver - Prozeßmodellierung, Systemtechnik, Eigenschaften laserstrahlgesinterter Metallkörper - Coremans, Adrianus (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1999)
Direct laser beam sintering of metal powders (DMLS) is still a young rapid prototyping process with great economic potential. Prototypes or prototype tools can be produced in a one-step process. The basics of the process must be better understood for qualified and controlled application. This was the first time in this work that: we developed a 3D process model that qualitatively describes the physical and material processes in the DMLS process. the influences of the process-determining parameters on component properties of laser-beam sintered workpieces are quantitatively and qualitatively recorded. we developed a process-adapted system technology to reduce the internal stresses introduced during laser beam sintering. Based on a structured process analysis, the three influencing factors laser beam, powder material and beam-material interaction were fundamentally characterized. The expansion of the knowledge gained with the analysis of the material properties of laser-sintered components provided the information to clarify the processes during laser beam sintering. Based on the understanding of laser beam internal in its entirety, a three-dimensional, physical process model was developed. During the first irradiation process, the powder material is converted into the solid, laser-sintered state. At the time the molten state occurs, there is adhesion to the surrounding substrate. The residual stresses are reduced during the subsequent irradiation. This modeling allows the effects on the characteristic component properties to be predicted qualitatively with a variation of the significant influencing parameters: the scanning speed primarily determines the achievable strengths with a tendency towards higher strengths at lower scanning speeds. the beam offset has a dominant influence on the internal stresses. An increase in the beam offset leads to greater tendencies to warp. Using the process model and practical test series, a process window for the powder material M Cu 2201 (components: Ni, CuSn, Cu-P and Cu3P) from EOS and the laser beam sintering system (manufacturer: EOS, type: EOSINT M 250) were determined. The surface energy introduced into the workpiece was determined as the main influencing factor. Mechanical properties, density, surface properties, tendency to warp and thermal stability of the components were characterized. As a result of the layered construction, laser-sintered workpieces have strongly anisotropic material properties. The changes in properties depending on the orientation to the normal of the building level, which amounted to up to 50% of the values of the mechanical component properties, could be predicted by the process model. Values for achievable mechanical component properties as a function of scan speed and beam offset are listed in Tables 7.3 and 7.4. A process window for which all the above-mentioned parameters reach an optimum does not exist. For example, an increase in strength is at the expense of the tendency to warp and good surfaces. To characterize the molded part geometry, the individual error sources were narrowed down and their effects were shown. The systematic analysis served as the basis for the development of an automatic calibration module, with the help of which the absolute inaccuracies could be reduced to a maximum of 0.15 mm and the relative to 0.15% of the total dimensions. This meant a 2.5-fold increase in dimensional accuracy compared to the uncalibrated delivery state of the investment. The temperature gradients between the interaction point and the surrounding, already sintered areas during the laser beam sintering led to internal stresses in the components, which in turn resulted in a distortion of the same. To reduce this effect, a flexible beam guidance and shaping system was developed. The raw beam emitted by the laser is divided into a focused working beam and a ring beam surrounding it, which is used to heat the surrounding powder bed. The comparison of workpieces, produced without and with process-adapted beam guidance, has shown that this concept of local preheating and postheating reduces the inherent stresses and the resulting distortion of the components by more than 50%. A specially developed test part was used, which allows the residual stresses introduced into the component by the laser beam sintering process to be determined quantitatively. In addition, the parts were significantly less warping even under thermal stress. Proof of this was provided by measurements of dimensional accuracy after heat treatments for a number of standardized components. The component properties determined in the course of this work and their qualitative prediction by means of the process model set up enable the user to tailor the properties of the laser-sintered components to the desired profile of requirements. Finally, this was exemplified using three selected applications. The possibility of quantitative predictions of the component properties is necessary for the further qualification of the laser beam internal. The extension of the physical process model to a quantitative description of the effects is an option. The use of FE analysis is suitable for support and expansion. The step-by-step structure of the 3D process model described in the present work represents a guideline for the development of numerical modeling. The component properties determined are available for the verification of the FE results. Furthermore, the material systems used offer great potential for improving the component properties of laser-sintered workpieces. The next step is to use steel as the low-melting component and to use a high-temperature resistant material such as tungsten as the high-melting component. In addition to this, the expansion of the system technology is a prerequisite, since the successful processing of oxidation-sensitive powder materials requires a reducing or inert atmosphere. The use of higher power laser beam sources enables the required higher process temperatures to be generated without reducing the scanning speed and thus the production time. By consistently implementing the results obtained, further areas of application can be opened up. Applications of laser beam internal e.g. for the production of molds for light metal die casting or for the forming technique or the production of electrodes for die sinking EDM are currently still in the research stage [REI97, GEI97]. However, you can already expect further technical and economic potential for industrial us